#UrbanAndMakingIt: Urban Youth's Visual Counternarratives of Being #MoreThanAStereotype. (January 2022) - Dunn, Alyssa Hadley; Neville, Mary L.; Vellanki, Vivek
The purpose of this study was to analyze the narratives constructed by urban youth in a summer program for future educators of color. In particular, we asked, "In what ways do students use texts to create counternarratives of urban education?" Utilizing visual counternarratives and counterstorytelling as theoretical frames, and through thematic analysis and visual amalgamated findings, we examined how students' written, visual, and audio texts countered stereotypes. Findings revealed that students used texts to create counternarratives of self, schools, and society.